Miradas ved(l)adas - Cannavacciuolo, Margherita (Ars et humanitas, 2015)
The present work considers the first short story by José Emilio Pacheco (1939-2014), "La sangre de Medusa" (1959), and his short novels El principio del placer (1972) and Las batallas en el desierto (1981), exploring for the first time their connections. The main issue is, on a thematic level, to individuate and analyse the Medusean figures in these texts, the construction of the female characters and of their relationships with male characters based on the narrative articulation of visual dynamics. On a formal level, the Gorgon's marks are traced to the constitutive limit of language. This work also studies the transition from a writing based on the blindness or visual incapacitation - and the consequent impossibility of expression - to a narrative based on a visual complexity, obtained by joining the past perspective of the narrated I and the present one of the narrating I.
Keywords: kratka proza; Medusean figures; Meduza; mehiška književnost; mexican short story; miti; mythology; myths; Pacheco; Pacheco, José Emilio